Prognostic value of cardiopulmonary exercise testing in cardiac amyloidosis. (22nd October 2020) - Nicol, Martin; Deney, Antoine; Lairez, Olivier; Vergaro, Giuseppe; Emdin, Michele; Carecci, Alessandro; Inamo, Jocelyn; Montfort, Astrid; Neviere, Remi; Damy, Thibaud; Harel, Stephanie; Royer, Bruno; et al.
Abstract : Aims: In amyloid patients, cardiac involvement dramatically worsens functional capacity and prognosis. We sought to study how the cardiopulmonary exercise test (CPET) could help in functional assessment and risk stratification of patients with cardiac amyloidosis (CA). Methods and results: We carried out a multicentre study including patients with light chain (AL) or transthyretin (TTR) CA. All patients underwent exhaustive examination including CPET and follow‐up. The primary prognostic endpoint was the occurrence of death or heart failure hospitalization. Overall, 150 patients were included (91 AL and 59 TTR CA). Median age, systolic blood pressure, N‐terminal pro B‐type natriuretic peptide (NT‐proBNP) and cardiac troponin T were 70 (64–78) years, 121 [interquartile range (IQR) 109–139] mmHg, 2806 (IQR 1218–4638) ng/L and 64 (IQR 33–120) ng/L, respectively. New York Heart Association classes were I–II in 64%. Median peak oxygen consumption (VO2 ) and circulatory power were low at 13.0 (10.0–16.9) mL/kg/min and 1730 (1318–2614) mmHg/mL/min, respectively. The minute ventilation/carbon dioxide production slope was increased to 37 (IQR 33–45). A total of 77 patients (51%) had chronotropic insufficiency. After a median follow‐up of 20 months, there were 37 deaths and 44 heart failure hospitalizations. At multivariate Cox analysis, peak VO2 ≤13 mL/kg/min [hazard ratio (HR) 2.7, 95% confidence interval (CI) 1.6–4.8], circulatory power ≤1730 mmHg/mL/min (HR 2.4, 95% CI 1.2–4.6) and NT‐proBNP ≥1800 ng/L (HR 2.2, 95% CI 1.1–4.3) were found to be associated with the primary outcome. No events occurred in patients with both peak VO2 >13 mL/kg/min and NT‐proBNP <1800 ng/L, while the association of VO2 ≤13 mL/kg/min with NT‐proBNP ≥1800 ng/L identified a very high‐risk subgroup. Conclusion: In CA, CPET is helpful in assessing functional capacity, circulatory and chronotropic responses as well as the prognosis of patients along with cardiac biomarkers. Abstract : Peak oxygen consumption and circulatory power are strong prognostic factors in cardiac amyloidosis.